COMPARATIVE EVALUATION OF DIETHANOLAMINE SOLUTION PURIFICATION TECHNOLOGIES FROM HEAT-STABLE SALTS AND BONDED AMINE - N.S. Ivanov; A.Z. Abilmagzhanov; I.Y. Adelbayev; A.E. Nurtazina (Academic Scientific Journal of Chemistry, 2020)
The article presents the comparative tests results of the purification of diethanolamine (DEA) aqueous solution by distillation method under reduced pressure and ion exchange from heat-stable salts (HSS) and a bound amine. It was shown that regardless of the cleaning method, there is a significant improvement in organoleptic characteristics (color, smell), but also in the foamy characteristics of solution. For industrial implementation, the vacuum distillation method can be described as mid-complexity, it requires the cost of solution’s heating, but its actualization does not require additional reagents. The addition of alkali could lead to extra increasing of amine concentration due to the return of the bound amine; however, distillation in the alkali presence is difficult due to its crystallization upon distillation of a significant part of the water. The distillation was carried out in two ways at a temperature of 130-1500 С: with the addition of alkali and without it, with the return of the first fractions to an additional extraction of ethanolamine. Distillation by the first method allowed you to extract about 2.5% of the amine and was not of practical interest. The distillation by the second method allowed to recover up to 88.2% of diethanolamine, at the same time, there was a complete purification from heat-stable salts and bound amine, foam characteristics also returned to normal. Various types of anion exchangers were tested: gel and several macroporous, of different alkalinity. A comprehensive assessment of anion exchangers of various manufacturers by several parameters was performed. Purification by ion exchange method allows you to increase the amine concentration in the purified solution due to its regeneration from the protonated form. The presented research work was carried out with a solution of regenerated diethanolamine from one of the oil refineries in Kazakhstan